1979
DOI: 10.1128/aac.15.4.547
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pyran on Latency After Herpes Simplex Virus Infections

Abstract: The immunomodulator pyran protected mice against both herpes simplex virus type 1 (HSV-1) and type 2 (HSV-2) infections. In infections of the lip with HSV-1, prophylactic administration of pyran reduced the severity of the herpetic lesions and enhanced their resolution, but did not decrease the high incidence of development of latent HSV-1 infection of the trigeminal ganglia. In vaginal infections with HSV-2, prophylactic administration of pyran either systemically or locally reduced mortality, reduced the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Considerable interest has recently been directed toward animal models of this infection which attempt to establish efficacy of antiviral treatments (15,20,21) and immunization procedures (7,23). We have demonstrated that infection ofthe lip with HSV-1 reproducibly causes the typical herpetic mucocutaneous lesion that can be monitored clinically and virologically (7,15). Similar to the human disease, there is limited mortality, and in the majority of mice the virus establishes latent infection in the trigeminal ganglion, which is readily accessible for determination of latent virus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable interest has recently been directed toward animal models of this infection which attempt to establish efficacy of antiviral treatments (15,20,21) and immunization procedures (7,23). We have demonstrated that infection ofthe lip with HSV-1 reproducibly causes the typical herpetic mucocutaneous lesion that can be monitored clinically and virologically (7,15). Similar to the human disease, there is limited mortality, and in the majority of mice the virus establishes latent infection in the trigeminal ganglion, which is readily accessible for determination of latent virus.…”
mentioning
confidence: 99%
“…These provide a basis for defining changes in the infectious process and immune responses that occur in immunized animals (7) or in animals treated with antiviral drugs or immunomodulators (15).…”
mentioning
confidence: 99%
“…When an ineffective hoof and mouth vaccine was given intraperitoneally simultaneously with pyran it resulted in 100% protection of mice; other work has shown anti-viral action even without vaccine adjuvancy: Morahan et al (46) demonstrated that pyran could protect mice in-vivo from herpes type 1 and type 2 (HSV) infection with reduction of both mortality and the severity of lesions. This use of IV pyran post herpes infection reduced virus titers and resultant pathogenesis suggesting that it may have value in early or latent herpes infection.…”
Section: Heparanase Inhibition: αντι-Met Astatic Effectsmentioning
confidence: 98%
“…The ability to model HSV-1 latency in mice (Morahan et al 1979) and rabbits (Shimomura et al 1983) has greatly advanced the understanding of virus reactivation (Webre et al 2012). However, VZV is a uniquely human virus and the lack of an animal model has hindered insight into its reactivation (Shahzad et al 2015).…”
Section: Introductionmentioning
confidence: 99%